2010
DOI: 10.1007/s11892-009-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Sequestrants for Lipid and Glucose Control

Abstract: Bile acids are generated in the liver and are traditionally recognized for their regulatory role in multiple metabolic processes including bile acid homeostasis, nutrient absorption, and cholesterol homeostasis. Recently, bile acids emerged as signaling molecules that, as ligands for the bile acid receptors farnesoid X receptor (FXR) and TGR5, activate and integrate multiple complex signaling pathways involved in lipid and glucose metabolism. Bile acid sequestrants are pharmacologic molecules that bind to bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 54 publications
0
51
1
4
Order By: Relevance
“…It has been hypothesized as a possible mechanism of lowering plasma cholesterol level. As a result, greater amount of cholesterol is converted to bile acids to maintain a steady level in the circulation [38]. Sriplang et al [39] suggested that O. stamineus aqueous extract might be useful in the control of diabetes, one of the obesity-associated risk factor.…”
Section: Lipase-inhibition Of Crude Plant Extractsmentioning
confidence: 99%
“…It has been hypothesized as a possible mechanism of lowering plasma cholesterol level. As a result, greater amount of cholesterol is converted to bile acids to maintain a steady level in the circulation [38]. Sriplang et al [39] suggested that O. stamineus aqueous extract might be useful in the control of diabetes, one of the obesity-associated risk factor.…”
Section: Lipase-inhibition Of Crude Plant Extractsmentioning
confidence: 99%
“…Активация TGR5 индуцирует продукцию ГПП-1 в энтероэндокринных клетках линии STC-1 и в экспериментальных исследованиях на мышах [15,16]. Кроме того, полусинтетическая желчная кислота, 6-этил-23(S)метилхолевая кислота (INT 777), которая является специфическим агонистом TGR5, индуцирует секрецию ГПП-1 в линии STC-1 и NCI-H716 клеток кишечника человека.…”
Section: молекулярные механизмы регуляции секреции инкретиновunclassified
“…In recent years, experimental and clinical studies have shown the effectiveness of bile acid-binding agents for treating type 2 diabetes (16,17). Some mechanisms of the glucose-lowering effect induced by bile acid-binding agents have been proposed, but the precise mechanisms are incompletely understood (18).…”
Section: Effects On Blood Chemistrymentioning
confidence: 99%